Uji Toksisitas dan Organoleptik dari Limbah Cair Kelapa Sawit pada Benih Ikan Nila (Oreochromis niloticus) - lena, nurhalena; Kurniadi, Bambang; Adijaya, Mardan (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2024)
Toxicity is the ability of a substance or chemical which, when exposed for a certain period, can cause damage to organisms. Factors that influence toxicity are composition, type, duration and frequency of exposure, recipient biota species and environmental characteristics. The results of this test describe the values LC50-96 hours or LC50-48 hours. The LC50 value is the concentration at which the extract solution can cause population death of up to 50%. This study aims to determine the concentration of acute toxicity of liquid palm oil waste on tilapia fish seeds and its effect on the organoleptic properties of tilapia. This research was carried out from May to July 2023 at the Aquatic Resources Management Laboratory, Faculty of Agriculture, Tanjungpura University. The method used is a static method in acute toxicity tests to determine the death of 50% of the number of test organisms. This research was carried out in 4 stages, namely preparation, preliminary test, toxicity test and treatment test. The toxicity test data was then analyzed using probit analysis. The LC50-96 hours value of palm oil liquid waste for the tilapia fish seed biota test is 4.88 mg/l. The LC50-96 hours value obtained from probit analysis is used to determine the TUa (Toxicity Unit Area) value by converting the LC50-96 hours value. The TUa value obtained was 20,49 indicating that the acute toxicity level of liquid palm oil waste causes acute toxicity.